An efficient and compact switch for quantum circuits. (December 2018) - Wu, Yulin; Yang, Li-Ping; Gong, Ming; Zheng, Yarui; Deng, Hui; Yan, Zhiguang; Zhao, Yanjun; Huang, Keqiang; Castellano, Anthony; Munro, William; Nemoto, Kae; Zheng, Dong-Ning; et al.
Abstract The engineering of quantum devices has reached the stage where we now have small-scale quantum processors containing multiple interacting qubits within them. Simple quantum circuits have been demonstrated and scaling up to larger numbers is underway. However, as the number of qubits in these processors increases, it becomes challenging to implement switchable or tunable coherent coupling among them. The typical approach has been to detune each qubit from others or the quantum bus it connected to, but as the number of qubits increases this becomes problematic to achieve in practice due to frequency crowding issues. Here, we demonstrate that by applying a fast longitudinal control field to the target qubit, we can turn off its couplings to other qubits or buses. This has important implications in superconducting circuits as it means we can keep the qubits at their optimal points, where the coherence properties are greatest, during coupling/decoupling process. Our approach suggests another way to control coupling among qubits and data buses that can be naturally scaled up to large quantum processors. Quantum circuits: coupling switch for quantum elements A method for switching on/off the coupling between quantum elements could assist in the scaling up of quantum circuits. Demonstrations of small-scale quantum processes made using multiple interacting quantum bits (qubits) is an important step towards the development of quantum computers. Scaling up the number of qubits to enable large-scale quantum processes is challenging, however, as it becomes difficult to control the couplings between them whilst maintaining their desirable properties. An international collaboration led by Xiaobo Zhu from the University of Science and Technology of China now demonstrate a simple approach for switching on and off the coupling between quantum elements. Such a protocol should enable qubits to be kept at their optimal conditions during (de)coupling processes, which could help in the development of large-scale quantum circuits.